1994
DOI: 10.1177/026921639400800307
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of midazolam during continuous subcutaneous administration in palliative ca re

Abstract: We have investigated the steady-state plasma concentrations of midazolam during continuous subcutaneous administration in palliative care. Using a sensitive gas chromatography with electron capture detector assay, plasma concentrations of midazolam were measured in 11 patients (median age 68 years; range 47-82 years; six females) receiving the drug by continuous subcutaneous infusion (median rate 20 mg/day; range 10-60 mg/day). While not significant, the infusion rate tended to decrease with increasing age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Moreover, in some studies the subcutaneous route was preferred because of lower complication risks. Only small and outdated prospective studies are available for midazolam, which all found subcutaneous administration of midazolam to be feasible and effective [ 39 , 43 , 44 ]. Regarding haloperidol, only retrospective descriptive studies or overview articles are available, even without addressing the administration route [ 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some studies the subcutaneous route was preferred because of lower complication risks. Only small and outdated prospective studies are available for midazolam, which all found subcutaneous administration of midazolam to be feasible and effective [ 39 , 43 , 44 ]. Regarding haloperidol, only retrospective descriptive studies or overview articles are available, even without addressing the administration route [ 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…[107] In palliative patients, no correlation was found between midazolam concentrations and liver disease, probably because liver diseases in this population are not as severe as in ICU patients. [108] Finally, CYP3A metabolism can also be affected by the use of other drugs. In the palliative setting, there might be a relevant interaction with dexamethasone.…”
Section: Midazolammentioning
confidence: 99%
“…Unfortunately the time it takes to reach adequate sedation varies widely between patients and awaking from a sedative state often occurs . A possible explanation for this might be large inter‐individual variability (IIV) in midazolam pharmacokinetics, which has already been shown in other populations . Large variability is also expected in terminally ill patients due to the heterogeneity of the population, including severe co‐morbidities (e.g.…”
Section: Introductionmentioning
confidence: 99%